The influence of consumer ethnocentrism, influencers, personal innovativeness, and cultural intelligence on the choice of foreign tourist destinations - Ivan Trifunović; Žaklina Spalević; Stefan Zdravković (BizInfo)
The process of globalization has implied greater interdependence of national cultures and economies, and the development of information technologies and transport services has made it easy to organize business and tourist trips to countries around the world. A certain group of people considers spending vacations at domestic tourist destinations a moral obligation and a patriotic act, while another group of people has a high level of innovativeness, follows fashion trends, technological innovations, stays informed about current events through social networks, has a pronounced openness to other cultures and different ideas, and frequently visits foreign tourist destinations. The research was conducted with the aim of examining the influence of consumer ethnocentrism, influencers, personal innovativeness, cognitive and motivational cultural intelligence on the respondents' decision to visit a foreign tourist destination. The field research was conducted using a survey method, and the respondents' answers (505) were analyzed using the Structural Equation Modeling (SEM) within the statistical package SmartPLS 4. The results showed that consumer ethnocentrism has a negative impact, while influencers, personal innovativeness, cognitive and motivational cultural intelligence have a positive impact on the respondents' decision to visit foreign tourist destinations. These findings are important for formulating an appropriate marketing strategy by service providers in the tourism and hospitality industry.